Avaliação da usabilidade e eficácia preliminar de um programa online de autocuidado baseado em Mindfulness nos níveis de Burnout em profissionais da Atenção Primária à Saúde (APS) - Favarato, Maria Lúcia [UNIFESP] (2018)
Objective: Developing and assessing the usability and preliminary efficacy of a Mindfulness-based Care Programs offered by self-directed learning (online) in the level of Burnout in the primary health care (PHC) professionals and generating knowledge could be included in the prospective guidelines for Burnout in the PHC. Methods: It is an uncontrolled naturalistic study with pre- and post-test measures. It is an uncontrolled naturalistic study with pre and post measurements. The intervention consists online Mindfulness course for two consecutive weeks (2 sessions of two and half-hours. 330 professional of health applied for study and only 112 were PHC. 78 professionals have completed the pre-test survey (before the mindfulness-based course). 27 PHC professionals obtained a value less than 9 – cut off point to inclusion in this study – and they were registered to participate in the mindfulness course. However, only 5 PHC professionals concluded the pre- and post-test measures. Results: Difference statistic revealed significant improvement in self-compassion scaled their subscale. However, the self-judgment, over-identification, and isolation increased significantly after the online course (p=0.067). The mindfulness level decreased in the all measures. The coefficient of friction between people concluded the course versus the non-people concluded the course revealed homogeneous data (p>0.05), with the exception of age (p= 0.005) (completers were 10 years older than non-completers in average). Nevertheless, a trend toward increased to anxiety level could be observed in the HADS scale, but it was not significant (p>0.05). Finally, self-compassion subscale, the subtype Common humanity revealed significant increase (p=0,083). Furthermore, the average of Mindfulnes (SCS) was higher than people concluded the course online (p=0,009). Conclusion: A brief mindfulness intervention may contribute to improving the common humanity of PHC professionals. The implementation of this program contributes to Burnout prevention, which has been reflected positively in the your emotions. However, its important to improve the adhesion of the mindfulness practices. More research using controlled and randomized designs are necessary to support found evidence in our study.